AN ECONOMIC ANALYSIS OF THE RELATIONSHIP BETWEEN AGRICULTURAL TRADE OPENNESS AND AGRICULTURAL GROWTH IN IRAQ FOR THE PERIOD (1990-2021). - Mhana , Noor; Al-Badri, Basim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The research was conducted to evaluate the link between agricultural trade openness and Iraqi agricultural development through the use of annual time series data from (1990–2021). This research that focuses on the Iraqi case study, as a developing country that opens up to the Global industry, and aims to identify the position of openness in facilitating agricultural development. The Research question centers around the effects of agricultural trade openness to agricultural growth or vice versa. The analysis is based on the examination of the secondary data utilizing statistics such as ARDL (Auto Regressive Distributed Lag) and co-integration analysis. The relevance of the findings results in understanding the complex causal relationship between agricultural trade openness and agricultural growth. The research conclusions indicate that the high agricultural trade openness index means that the Iraqi economy is highly dependent on the outside world, which weakens the economic and political ability to confront fluctuations in economic activity. The impact of the agricultural trade openness policy in Iraq depends on the performance of the economy in general and the quality of imported goods in particular. The co-integration test of the ARDL model shows the existence of a long-term balanced relationship between the dependent variable. The research recommends the need to enhancement the competitiveness of major agricultural products and adopts encouraging policies to enhance export. It also highlights the importance of developing effective agricultural policies that provide the necessary support to farmers, to adapt to the changes resulting from trade openness.